Quantitative polymerase chain reaction assay for serum hepatitis B virus DNA as a predictive factor for post-treatment relapse after lamivudine induced hepatitis B e antigen loss or seroconversion. Issue 12 (21st November 2003) - Lee, H C; Suh, D J; Ryu, S H; Kim, H; Shin, J W; Lim, Y-S; Chung, Y-H; Lee, Y S
Abstract : Background and aims: Lamivudine induces favourable virological and biochemical responses but post-treatment relapses are frequent, even in patients with hepatitis B e antigen (HBeAg) loss or seroconversion. The aim of this study was to determine whether extended lamivudine therapy for up to 12 months after HBeAg loss/seroconversion could decrease the risk of post-treatment virological relapse. In addition, we monitored serum hepatitis B virus (HBV) DNA levels using a quantitative polymerase chain reaction (PCR) assay during extended lamivudine therapy and analysed predictive factors for post-treatment relapse. Patients and methods: A total of 49 patients who exhibited HBeAg loss/seroconversion during lamivudine therapy received extended lamivudine therapy for six months (group 1, n = 23) or 12 months (group 2, n = 26) after HBeAg loss/seroconversion. Serum HBV DNA levels were quantified by a PCR based assay at the time of HBeAg loss/seroconversion, and at cessation of therapy. Results: Post-treatment virological relapse rates at two years were 59% in group 1 and 50% in group 2. Age, time interval to HBeAg loss/seroconversion, and serum HBV DNA levels at the time of cessation of therapy were independent predictive factors for post-treatment relapse. The post-treatment relapse rate was 37% at two years in patients with serum HBV DNA levels of <200 copies/ml but 73% in those with ⩾10 3 copies/ml. Conclusions: Extended lamivudine therapy for up to 12 months did not decrease the rate of post-treatment virological relapse, and monitoring of serum HBV DNA by a quantitative PCR method was helpful in predicting post-treatment relapse.